Pengaruh Kualitas Pelayanan Trolleyman terhadap Kepuasan Penumpang di Terminal 2 Bandar Udara Internasional Soekarno-Hatta - Sistianingsih, Alya; Dewantari, Aditya (Jurnal Manajemen Dirgantara, 2025)
Air transportation has become the primary choice for long-distance travel due to its speed and efficiency. The quality of airport services plays a crucial role in shaping passenger satisfaction, including supporting services such as trolley facilities. Trolley attendants, as frontline personnel, are responsible for ensuring the availability, cleanliness, and proper arrangement of trolleys, as well as offering friendly and responsive service to airport users. This study aims to determine the effect of trolley attendant service quality on passenger satisfaction at Terminal 2 of Soekarno-Hatta International Airport. This study uses a quantitative method with a survey approach. The population consists of passengers who have used trolley services at Terminal 2, with a total of 100 respondents selected using a random sampling method. Data were collected using a Likert scale questionnaire and analyzed using Simple Linear Regression Analysis, T-Test, and R-Square Test. The results of the study indicate a significant effect of trolley attendant service quality on passenger satisfaction. The significance value obtained from the Coefficient table is 0.000 < 0.05, and the R-Square value is 0.715. This means that 71.5% of passenger satisfaction is influenced by the quality of trolley attendant service, while the remaining 28.5% is influenced by other variables not examined in this study. These findings emphasize the importance of maintaining high-quality trolley service to improve the overall passenger experience at the airport.